Comparison of arm-hand bimanual intensive therapy and current therapy for unimanual and bimanual functions in children with cerebral palsy - Sayed Mohammad Sadegh Hosseini; Hosein Sourtiji; Atefeh Taghizadeh (Vesnu Publications, 2012)
Introduction: Studies have showed that although Constraint Induced Movement Therapy can lead into improvement of hand function in children with Cerebral Palsy, it has several important limitations. Charles and Gordon introduced Hand-Arm Bimanual Intensive Therapy (HABIT) in an attempt to compensate for such deficits. This study aimed at evaluating the efficacy of HABIT on unimanual and bimanual functions in children with Cerebral Palsy. Materials and Methods: The participants of this single-blinded randomized control study were twenty-eight children with CP who were divided into two groups of HABIT and controls according to a set of inclusionary and exclusionary criteria. Subjects in HABIT group received the intervention 6 hours per day over 10 successive days and the members of the other group were provided with occupational therapy services. Assessment tools administered in this study were Bruininks-Oseretsky Test of Motor Proficiency, Caregiver Functional Use Survey (CFUS), and Jebsen-Taylor Test in Hand Function. Independent and paired t tests were respectively used for comparing the two groups and to compare each group with regard to pre-test and post-test conditions. Results: Study results showed significant differences between two groups concerning dexterity, bilateral coordination, bimanual coordination, bimanual function, unimanual function and Caregiver Functional Use Survey (how well & how frequently) (P < 0.05). Also comparison of pre-test and post-test results for each of the two studied groups indicated improvement in most of domains evaluated. Conclusion: The protocol of Arm-Hand Bimanual Intensive Therapy may result in improvement of either bimanual or unimanual hand functions in children with cerebral palsy. Keywords: Arm-Hand bimanual intensive therapy, Hand function, Hemiplegia, Occupational therapy